2007
DOI: 10.1002/jnr.21582
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of MAb6B4 epitopes on chondroitin sulfate proteoglycan aggrecan in perineuronal nets from cerebral cortices of SAMP10 mice: A model for age‐dependent neurodegeneration

Abstract: The accelerated senescence-prone SAMP10 mouse strain is a model for age-dependent neurodegeneration and is characterized by brain atrophy and deficits in learning and memory. Because perineuronal nets play an important role in the synaptic plasticity of adult brains, we examined the distributions of molecules that constitute perineuronal nets in SAMP10 mouse brain samples and compared them with those in control SAMR1 mouse samples. Proteoglycan-related monoclonal antibody 6B4 (MAb6B4) clearly immunostained per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…While both Cat-315 and 6B4 have been shown to primarily detect carbohydrate epitopes on RPTPζ/phosphacan in the early developing brain these antibodies largely detect carbohydrate epitopes on aggrecan and PNs in the adult brain (Matthews et al, 2002; McRae et al, 2007; Saitoh et al, 2008). Given that the immunoreactivity of both Cat-315 and 6B4 on RPTPζ/phosphacan were dramatically reduced in the cortex of embryonic and early postnatal POMGnT1 knockout animals, the reactivity of these antibodies were evaluated in the cortex of adult POMGnT1 knockout animals to determine if their carbohydrate epitopes present on aggrecan were also lost in the absence of O -mannosyl linked glycans.…”
Section: 3 Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While both Cat-315 and 6B4 have been shown to primarily detect carbohydrate epitopes on RPTPζ/phosphacan in the early developing brain these antibodies largely detect carbohydrate epitopes on aggrecan and PNs in the adult brain (Matthews et al, 2002; McRae et al, 2007; Saitoh et al, 2008). Given that the immunoreactivity of both Cat-315 and 6B4 on RPTPζ/phosphacan were dramatically reduced in the cortex of embryonic and early postnatal POMGnT1 knockout animals, the reactivity of these antibodies were evaluated in the cortex of adult POMGnT1 knockout animals to determine if their carbohydrate epitopes present on aggrecan were also lost in the absence of O -mannosyl linked glycans.…”
Section: 3 Resultsmentioning
confidence: 99%
“…Previous work has shown that both Cat-315 and 6B4 primarily detect carbohydrates on RPTPζ/phosphacan early in development (Dino et al, 2006; Maeda et al, 1994) and on aggrecan in the adult brain (Matthews et al, 2002, McRae et al, 2007, Saitoh et al, 2008). Therefore, while the reactivity of these antibodies for RPTPζ/phosphacan was eliminated, surprisingly it was essentially unaffected on aggrecan localized to PN structures.…”
Section: 4 Discussionmentioning
confidence: 99%
“…The SAMP10 strain of mice is a model of brain aging in which senescence is characterized by cerebral atrophy and several neurodegeneration phenotypes [46][47][48][49][50]. Recently, some molecular abnormalities have been identified in SAMP10 mice, including the absence of normal fibroblast growth factor 1 protein [51] and a reduced expression of MAb6B4 epitopes on aggrecan in perineuronal nets from the cerebral cortices [52]. However, whether these molecular alterations have a causal relationship with neurodegeneration remains to be elucidated.…”
Section: A Higher Oxidative Stress Status Is a Primary Characteristicmentioning
confidence: 99%
“…The contribution of such diversity to PNN composition has been, to some extent, investigated using antibodies raised against core proteins and specific sulfation patterns (Bertolotto et al, 1996; Caterson, 2012; Hagihara et al, 1999; Haunso et al, 1999; Hayashi et al, 2007; Madinier et al, 2014; Matthews et al, 2002; Miyata et al, 2012; Nakamura et al, 2009; Ojima et al, 1998; Racz et al, 2014; Saitoh et al, 2008; Yin et al, 2006), as well as lectins such as wisteria floribunda agglutinin (WFA). WFA, perhaps the most widely used in studies of PNNs, binds specifically to N-acetyl-D-galactosamine on the terminal end of CS chains, with a preference for beta glycosidic linkage (Kurokawa et al, 1976; Young and Williams, 1985).…”
Section: Perineuronal Nets: Composition and Association With Distimentioning
confidence: 99%